2021
DOI: 10.1038/s41420-021-00733-4
|View full text |Cite
|
Sign up to set email alerts
|

DACH1 inhibits breast cancer cell invasion and metastasis by down-regulating the transcription of matrix metalloproteinase 9

Abstract: Human Dachshund homolog 1 (DACH1) is usually defined as a tumor suppressor, which plays an influential role in tumor growth and metastasis in a variety of cancer cells. However, the underlying mechanisms in these process are not yet fully clarified. In this study, DACH1 inhibited the invasion and metastasis of breast cancer cells by decreasing MMP9 expression. Mechanistically, DACH1 represses the transcriptional level of MMP9 by interacting with p65 and c-Jun at the NF-κB and AP-1 binding sites in MMP9 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Our results indicated that Dox dose-dependently decreased the expression of c-Jun in the nucleus extracts of both cellular variants ( Figure 3 F,G), which possibly explains the changes in MMP-9 secretion in the extracellular medium. Although a regulatory mechanism mediated by the AP-1 complex and, therefore c-Jun is carried out, other mechanisms could have also been involved, including the activity of the tumor suppressor DACH1 (Dachshund Homolog 1) [ 57 ], miR-194-5p [ 58 ], and decreases in sirtuin 6 [ 59 ]. Moreover, a potential association between PDCD4 and c-Jun signaling was suggested by the expression of miR-21, which promotes the migration, invasion, and angiogenic capacity of renal carcinoma cells [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that Dox dose-dependently decreased the expression of c-Jun in the nucleus extracts of both cellular variants ( Figure 3 F,G), which possibly explains the changes in MMP-9 secretion in the extracellular medium. Although a regulatory mechanism mediated by the AP-1 complex and, therefore c-Jun is carried out, other mechanisms could have also been involved, including the activity of the tumor suppressor DACH1 (Dachshund Homolog 1) [ 57 ], miR-194-5p [ 58 ], and decreases in sirtuin 6 [ 59 ]. Moreover, a potential association between PDCD4 and c-Jun signaling was suggested by the expression of miR-21, which promotes the migration, invasion, and angiogenic capacity of renal carcinoma cells [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, further significantly upregulated genes such as DOCK10, GPC6, and FSCN1 have been related to enhanced tumor cell migration and/or invasion [67][68][69][70]. In contrast, several factors assigned to the suppression of tumor cell migration and/or invasion as well as angiogenesis, such as DLC1, RHOU, DACH1, and RECK, were significantly downregulated in the brain-seeking cell line in comparison with the native one [71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 96%
“…Western blotting analysis showed that RARαS77A upregulated the epithelial marker E-cadherin while reducing the expression of ZEB1 (a transcriptional repressor that allows cancer cells to invade and spread) and the cytoskeletal protein β-catenin, both of which are reliable prognostic markers of solid tumor aggressiveness [25]. In addition, RARαS77A downregulated MMP2, a collagenase that can degrade the extracellular matrix to promote the invasion and metastasis of tumor cells [26,27]. Thus, the suppression of EMT is likely to be a major contributor to the antimetastatic action of RARαS77A.…”
Section: Discussionmentioning
confidence: 99%